Evaluation of chloride migration in ultra-high performance concrete (UHPC) with glass powder - Vitoretti Dias, Lucas; Mari Soares, Silvete; Alves Salvador Filho, José A.; Ferreira, Fernanda Giannotti da Silva (Revista ALCONPAT, 2021)
The influence of glass powder incorporation to ordinary concrete regarding mechanical and durability properties has been studied. This work aims to evaluate the durability of ultra-high performance cementitious composites (UHPCC) with partial substitution of Portland cement by glass powder, through chloride migration test according to the NT Build 492 methodology. With this aim, specimens with 0%, 10%, 20%, 30% and 50% content of glass powder by weight of Portland cement were cast, cured in lime saturated water until the age of 28 days. The results indicate that minor contents of glass powder do not harm the concrete properties and higher contents maintain good mechanical and durability characteristics.